PENGARUH FAKTOR PSIKOLOGIS DAN FAKTOR KEPRIBADIAN TERHADAP KEPERCAYAAN PELANGGAN DAN DAMPAKNYA PADA PARTISIPASI PELANGGAN E-ECOMMERCE DI INDONESIA - Ridwan, Muhamad (LPPM UNIVERSITAS BINA INSAN, 2019)
This study aims to analyze the influence of psychological factors and personality factors on customer trust and its impact on the participation of e-commerce customers in Indonesia. This type of causal research with the population of all e-commerce customers with sampling technique Purposive sampling. The research sample was 192 people, obtained from number of indicator 32 multiplied by 6 (Hair et al, 2011). Data analysis of Strucutural Equation Model (SEM) with Partial Least Square Software (PLS) version 3.00. The result of this research show that psychological factor have positive and significant influence to customer's trust, personality factor have positive and significant effect to customer's trust, and customer's trust have positive and significant influence to e-commerce customer's participation in Indonesia. Advice for Vendor e-commerce service providers to improve communication, experience and service, provision of quality products, wider knowledge, self-existence, distributors and delivery services to customers, because the results of this study states the ability dimensions (ability) being the most powerful dimension of its correlation coefficient with repeated purchasing dimensions on customer participation variables. If the ability of consumers to increase their confidence in e-commerce transactions then the decision to make repeat purchases in e-commerce transactions will be higher.